Environment-adaptable photonic-electronic-coupled neuromorphic angular visual system - Kumar, Mohit; Lim, Jaeseong; Kim, Sangwan; Seo, Hyungtak (ACS Nano, 2020)
Environment-adaptable photonic-electronic-coupled devices can help overcome major challenges related to the extraction of highly specific angular information, such as human visual perception. However, a true implementation of such a device has rarely been investigated thus far. Herein, we provide an approach and demonstrate a proof-of-concept solid-state semiconductor-based highly transparent, optical-electrical-coupled, self-adaptive angular visual perception system that can fulfill the versatile criteria of the human vision system. Specifically, all of the primitive functions of visual perception, such as broad angular sensing, processing, and manifold memory storage, are demonstrated and comodulated using optical and electric pulses. This development represents an essential step forward in the fabrication of an environment-adaptable artificial angular perception framework with deep implications in the fields of optoelectronics, artificial eyes, and memory storage applications.
Keywords: Coupled devices; Human vision systems; Human visual perception; Primitive function; Proof of concept; Solid state semiconductors; Visual perception; Visual systems; Angular perception; Highly transparent; Photonic; Schottky junction; Visual memory